A Comprehensive Evaluation of Multimodal Analgesia Techniques in Postoperative Pain Administration: Dealing with the Opioid Crisis by Novel Orthopedic Surgery Approach - Al-Qarni, Adel Abdullah Ali; Daghreri , Ghada Abodosa Jaber; Alamri, Saleh Mohammed Ahmed; Daghriri, Laila Abodosa Jaber; Dagreri, Noora Abudossa Jaber; Almalki, Saad Abdullah; Alghamdi , Ashwaq Ali; Alotebi, Ghazi Saud Marzoq; Alrumayh, Rumayh Abdulah; Malakah , Noha Ashari; Faqiri, Hatim Hamad Ibrahim; Al-Qahtani, Abdullah Awad Shujaa; et al. (Journal of Ecohumanism, 2024)
Background: The opioid epidemic has made efficient painkillers with little dependency on opioids desperately needed. Especially in orthopedic operations, multimodal analgesia (MMA) has become a complete strategy for controlling postoperative pain. Methods: With an eye on their effectiveness in lowering postoperative pain and opioid use, this review looks at the present research on multimodal pain treatment techniques. Studies on many analgesic approaches—including pharmacological and non-pharmacological approaches—were searched methodically through several databases. Results: The study shows that multimodal analgesia—which incorporates many types of analgesics and approaches—significantly lowers the pain management need for opioids using diverse class of analgesics. Positive results have come from regional anesthetic, systemic non-opioid analgesics, and auxiliary treatments (e.g., physical therapy, and psychological support). Research shows that MMA could cause shorter hospital stays, lower pain levels, and more patient satisfaction. Conclusions: In orthopedic patients, multimodal analgesia is a good approach for controlling postoperative pain. Combining many approaches to pain management helps doctors maximize healing and reduce the risk of problems connected to opioids. To help further enhance patient outcomes, future studies should concentrate on standardizing multimodal procedures and investigating creative analgesic approaches